GenderUp training workshop for Ukama Ustawi initiative partners in Zambia - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
This video was taken during the training workshop on responsible and inclusive scaling of agricultural innovations using the GenderUp Methodology held from 11-12 November, 2024 with Ukama Ustawi Initiative scaling partners in Lusaka, Zambia. The training was organized by the International Institute of Tropical Agriculture (IITA) by bringing together a diverse group of stakeholders from various active scaling projects in Zambia for collaboration and shared learning on inclusive scaling. The video showcases why the training was conducted as well as the outcome of the training based on participants' own voices. This work is part of Ukama Ustawi Initiative’s Work Package 5 (WP5) work on “Empower and Engage". This publication has been prepared as an output of the One CGIAR Initiative Ukama Ustawi: Diversification for Resilient Agribusiness Ecosystems in East and Southern Africa. This work was carried out under the One CGIAR Initiative Ukama Ustawi (UU), which is grateful for the support of CGIAR Trust Fund contributors (www.cgiar.org/funders).